Is labour market discrimination against ethnic minorities better explained by taste or statistics? A systematic review of the empirical evidence. Issue 17 (5th October 2022) - Lippens, Louis; Baert, Stijn; Ghekiere, Abel; Verhaeghe, Pieter-Paul; Derous, Eva
ABSTRACT: To mitigate ethnic labour market discrimination, it is essential to understand its underlying mechanisms because different mechanisms call for different counteracting measures. To this end, we reviewed the recent literature that confronts the theories of taste-based and statistical discrimination against the empirical reality. Whereas the empirical evidence for both mechanisms is generally mixed, (field) experimental research, which predominantly focuses on hiring outcomes, appears to yield proportionately more evidence in favour of taste-based discrimination vis-à-vis statistical discrimination. This finding suggests that the taste-based mechanism may better explain ethnic discrimination in hiring. However, we also observe that the measurement operationalisations of the mechanisms vary substantially between studies and that alternative theoretical interpretations of some of the evidence are plausible. Taken together, additional research efforts, using clear measurement standards and appropriate synthesis methods, are required to solidify the review's main finding.